{Erratum to ‘Exploring and exploiting the systemic effects of deregulated replication licensing' [Seminars in Cancer Biology 37–38C, (2016) 3–15]} - Petrakis, Theodoros G.; Komseli, Eirini-Stavroula; Papaioannou, Marilena; Vougas, Kostas; Polyzos, Alexandros; Myrianthopoulos, Vassilios; Mikros, Emmanuel; Trougakos, Ioannis P.; Thanos, Dimitris; Branzei, Dana; Townsend, Paul; Gorgoulis, Vassilis G (Seminars in Cancer Biology, 2017)
In Fig. 4a the heat map legend is as follows: [figure presented]